2022
DOI: 10.1186/s12866-022-02579-x
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans DAF-16 regulates lifespan and immune responses to Cryptococcus neoformans and Cryptococcus gattii infections

Abstract: Background Cryptococcosis is a life-threatening infection is primarily caused by two sibling species Cryptococcus neoformans and Cryptococcus gattii. Several virulence-related factors of these cryptococci have been widely investigated in Caenorhabditis elegans, representing a facile in vivo model of host–pathogen interaction. While recent studies elucidated cryptococcal virulence factors, intrinsic host factors that affect susceptibility to infections by cryptococci remain unclear and poorly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Thus, we employed this transgenic C. elegans strain (BZ555) to visualize the DA neurons in a living animal. We previously reported that C. neoformans and C. gattii can accumulate and kill the wildtype (N2) C. elegans ( Kitisin et al., 2022 ). In the present study, we found that accumulation of C. neoformans and C. gattii yeast cells in the distended gastrointestinal tract was anatomically close to 6 DA neurons ( Figures 1A, B ) ( Harrington et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we employed this transgenic C. elegans strain (BZ555) to visualize the DA neurons in a living animal. We previously reported that C. neoformans and C. gattii can accumulate and kill the wildtype (N2) C. elegans ( Kitisin et al., 2022 ). In the present study, we found that accumulation of C. neoformans and C. gattii yeast cells in the distended gastrointestinal tract was anatomically close to 6 DA neurons ( Figures 1A, B ) ( Harrington et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we employed this transgenic C. elegans strain (NL5901) to visualize the accumulation of human α-synuclein in a living animal. We have previously reported that infections of C. neoformans and C. gattii can accelerate the aging process and reduce the lifespan of C. elegans involving with IIS/DAF-16 pathway ( Kitisin et al., 2022 ). A recent study has also reported that accumulation of aggregated human α-synuclein inclusions was strongly associated with the activation of DAF-16 suggesting the relationship between the IIS pathway and PD ( Haque et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations